Analisis Kesalahan Umum dalam Penyusunan Makalah Akademik: Studi Kasus Mahasiswa Perguruan Tinggi - Zahra, Hafizha; Padang, Chelsea Beatrice; Sianturi, Tiurmaida; Nazwa, Syahira; Audina, Rizka; Dalimunthe, Syairal Fahmy (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze errors in scientific writing by students in several universities in Indonesia, identify the factors that cause them, and provide recommendations for improvement. This study uses a quantitative descriptive method with a questionnaire survey distributed to 100 students from various universities in North Sumatra selected by convenience sampling method. The questionnaire covered understanding of paper format, frequency of writing, level of difficulty, training experience, factors causing errors, and proposed solutions. The results showed that students generally have a good understanding of the basic structure of term papers, but there are still weaknesses in technical aspects such as spacing, margins, and title writing. Factors causing errors include lack of understanding of the material, technical formatting errors, and lack of attention to detail. This study recommends more specific and practical writing training to improve the quality of students' academic writing.